Characteization and evaluation of nutmeg (Myristica fragrans Houtt.) accessions - Vikram H C (Department of Plantation Crops and Spices, College of Horticulture, 2016)
Nutmeg (Myristica fragrans Houtt.) is an introduced crop to India. There exists tremendous variability in the nutmeg population in Kerala, which is the major nutmeg growing state in the country. Assessment of the existing variability is a prerequisite for taking up successful crop improvement programmes, which is very much limited in this tree spice. In this context, the present study entitled “Characterization and evaluation of nutmeg (Myristica fragrans Houtt.) accessions” was taken up exclusively with the specific objectives to characterize nutmeg accessions based on morphological, biochemical and molecular parameters so as to scale the variability in a multidimensional way. Select fifty nutmeg accessions from a core germplasm collected and maintained in a private plantation in the Chalakudy river basin, belonging to age of fifteen years, formed the material for the study. Among the select fifty accessions, forty two were females, four monoecious and four males. In the morphological characterization, 51 qualitative and 38 quantitative characters were recorded from two trees per accession. Biochemical characterization was done in the select seventeen distinct accessions. GC-MS profiling was done in kernel and mace oils. Biochemical constituents of fresh pericarp were estimated. Isozyme profiling was done for peroxidase and polyphenol oxidase enzymes. The molecular characterization was attempted with 21 RAPD and 12 ISSR primers after screening. A key for identification of an elite nutmeg tree was developed. A descriptor for nutmeg with a set of 51 qualitative and 38 quantitative parameters and descriptor states for each of these characters was developed as the first step. This is the first study of its kind to develop a minimal descriptor for nutmeg. The descriptor developed from the present study was simultaneously utilised for morphological characterization and evaluation of the accessions. Wide variability was noticed among the accessions for 47 out of 51 qualitative characters. Four characters viz., leaf margin, fruit pubescence, grooves on nut and nature of fruit dehiscence were noted as non variable characters and hence, these were not included for further analysis. Based on the qualitative characters, accessions were classified into 11 clusters at 66 per cent similarity level. Accessions differed significantly for all the quantitative characters except shelling percentage. Performance evaluation of the accessions brought out the superiority of accession 8, 9 and 22 for yield. The accessions showed high GCV, PCV, h2 and genetic gain for most of the characters. Number of fruits per tree, fruit set percentage, number of fruits per m2, fresh and dry weight of mace, mace volume as well ratio of nut to mace exhibited high genetic gain. Hence, selection programme based on these characters will be very effective in improving the base populations. Based on Mahalanobis D2 analysis, accessions were grouped into 10 clusters. Wide range of variation was observed in contents of volatile oil, oleoresin and fixed oil of kernel and mace. Based on these constituents accessions were grouped into 26 clusters, which indicated their distinct quality. Based on the results of the morphological characterization, seventeen distinct accessions were selected for further biochemical and molecular analysis. GC-MS analysis of kernel and mace oils exhibited 20 and 24 constituents respectively. Volatile oil composition exhibited wide variability for the major constituents viz., myristicin, elemicin, safrole and sabinene apart from the presence of some unique compounds. Grouping of the accessions was done based on the per cent content of these important compounds. Two accessions recorded high contents of both myristicin and elemicin whereas another two accessions were in the complimentary; belonging to low myristicin group. High sabinene combined with low myristicin was the intrinsic quality attribute of one of the accessions. Change, as well as addition/deletion of specific constituents was also noticed in the volatile oils after storage for one year. Accessions exhibited wide range of variation in the biochemical constituents of pericarp, a valuable information for the value addition of pericarp. Total phenol and tannins exhibited high variation. The accessions were ranked based on the content of biochemical constituents. Isozyme profiling using peroxidase enzyme produced four bands and that based on polyphenol oxidase exhibited three bands. Molecular markers could assess the variability among the accessions. The selected 21 RAPD primers produced a total of 164 amplicons of which 63.21 per cent were polymorphic. The 12 ISSR primers selected produced a total of 87 amplicons of which 69.44 per cent were polymorphic. Few unique bands were detected for specific characters. Inter cluster association of each of the qualitative clusters with other clustering patterns was worked out. The results indicated the differences as well as similarities of the qualitative clusters with other clustering patterns. Finally, key quantitative characters were identified based on their direct and indirect effect on yield as also economic importance. The statistical key thus developed using 13 key quantitative characters will serve as a preliminary tool for identification of an elite nutmeg tree.